2021
DOI: 10.3390/coatings11040377
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Phase Formation, and Superconducting Properties of Bulk YBa2Cu3Oy Superconductors Grown by Infiltration Growth Process Utilizing the YBa2Cu3Oy + ErBa2Cu3Oy + Ba3Cu5O8 as a Liquid Source

Abstract: The infiltration growth (IG) process is well-known as the most established technique consisting of Y2BaCuO5 (Y211) precursor powders and liquid phases toward the fabrication of bulk YBa2Cu3Oy (Y123) superconductor for high field industrial applications. We have reported the fabrication of Y123 bulks using this technique at various ratios of liquid phase source. In this study, the use of liquid phase source toward the infiltration growth of bulk Y123 superconductors at different ratios of Y123 and ErBa2Cu3Oy (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous research has indicated that the presence of impurities in nanoparticles can serve in two ways: they can act as pinning centers that immobilize vortices or enhance the interconnection among the grains. This, in turn, can potentially enhance the critical current density J c [54,55]. The crystallite size listed in Table 2 was calculated by choosing the highest peak and using the Scherrer equation [56]:…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…Previous research has indicated that the presence of impurities in nanoparticles can serve in two ways: they can act as pinning centers that immobilize vortices or enhance the interconnection among the grains. This, in turn, can potentially enhance the critical current density J c [54,55]. The crystallite size listed in Table 2 was calculated by choosing the highest peak and using the Scherrer equation [56]:…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…The discovery of superconductivity in YBa 2 Cu 3 O 7~δ (Y123) compounds have attracted significant attention around the world due to its high critical temperature (T c ), the ability to be cooled to the superconducting state by the cheap LN 2 and their promising ability in numerous technological applications, including in real life such as in magnetic levitation transportations system and high power transmission cables [1][2][3]. Various studies have investigated the synthesis of Y123 with different characteristics and parameters [4][5][6][7][8][9][10][11] However, many researchers are still looking to find the ideal way to produce a Y123 compound with better superconducting properties.…”
Section: Introductionmentioning
confidence: 99%